Understanding the Chemical and Physical Transformations of a Ziegler–Natta Catalyst at the Initial Stage of Polymerization Kinetics: The Key Role of Alkylaluminum in the Catalyst Activation Process. Issue 18 (19th May 2014) - Dwivedi, Sumant; Taniike, Toshiaki; Terano, Minoru; Sun, Wen‐Hua
<x xml:space="preserve">Abstract</x> An improved stopped‐flow (SF) technique is employed to clarify the origin of kinetics in propylene polymerization with a Mg(OEt)2‐based Ziegler–Natta catalyst. Polymerization in the range of 0.1–5 s exhibits a kinetic transition from a linear development to a build‐up‐type development of the yield. It is found that a lower alkylaluminum concentration leads to a lower activity in the linear regime, whereas the extent of the activation becomes greater in the build‐up regime. The origin of these kinetic behaviors is studied using scanning electron microscopy (SEM) for catalyst/polymer particles and cross‐fractionation analyses for polymer structures. It is found that the kinetic transition mainly arises from the fragmentation of the catalyst particles and resultant increase in the active site concentration. The fragmentation manner strongly depends on the alkylaluminum concentration, which affects not only the amount, but also the placement of initial polymer formation. The nature of the active sites varies as a result of an aging effect with alkylaluminum: their stereospecificity, propagation rate constant, and tolerance for chain transfer reaction increase as the polymerization progresses. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>